2008
DOI: 10.4049/jimmunol.181.9.6051
|View full text |Cite
|
Sign up to set email alerts
|

IL-24 Induces Apoptosis of Chronic Lymphocytic Leukemia B Cells Engaged into the Cell Cycle through Dephosphorylation of STAT3 and Stabilization of p53 Expression

Abstract: Chronic lymphocytic leukemia (CLL) is characterized by the accumulation of long-lived monoclonal B cells mostly arrested at the G0/G1 phase of the cell cycle. CLL cells strongly express intracellular melanoma differentiation-associated gene-7 (MDA7)/IL-24. However, adenovirus-delivered MDA7 was reported to be cytotoxic in several tumor cell lines. We report herein that rIL-24 alone had no effect; however, sequential incubation with rIL-2 and rIL-24 reduced thymidine incorporation by 50% and induced apoptosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 54 publications
(55 reference statements)
4
26
1
Order By: Relevance
“…This is similar to a previous finding that IL-24 induces apoptosis of chronic lymphocytic leukemia B cells through a mechanism of dephosphorylation of STAT3 and stabilization of p53 expression by phosphorylating p53 (Ser15). 22 In this study, AA induced TEC apoptosis by activating the p53 pathway via inactivation of the p53 repressor STAT3. Addition of AA also induces the dephosphorylation of STAT3, leading to stabilization of p53 by increasing p53 (Ser15) phosphorylation and protein accumulation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This is similar to a previous finding that IL-24 induces apoptosis of chronic lymphocytic leukemia B cells through a mechanism of dephosphorylation of STAT3 and stabilization of p53 expression by phosphorylating p53 (Ser15). 22 In this study, AA induced TEC apoptosis by activating the p53 pathway via inactivation of the p53 repressor STAT3. Addition of AA also induces the dephosphorylation of STAT3, leading to stabilization of p53 by increasing p53 (Ser15) phosphorylation and protein accumulation.…”
Section: Discussionmentioning
confidence: 66%
“…22 Addition of AA (5 g/ml) caused dephosphorylation of phospho-STAT3 (Tyr705), thereby reducing STAT3 protein expression in a time-and dosage-dependent manner (Figure 10). The functional role of phospho-STAT3 in protecting AA-mediated TEC apoptosis via the p53 pathway was further demonstrated by the finding that overexpression of STAT3 in TECs rescued AA-induced (5 g/ml) dephosphorylation of STAT3, thereby inhibiting AA-induced p53 phosphorylation and p53 protein accumulation and p53-mediated apoptosis demonstrated by cleaved caspase-3 and TUNEL ϩ TECs (Figure 11).…”
Section: Aa Induces Phosphorylation Of P53 Via a Stat3-dependent Mechmentioning
confidence: 99%
“…The results from IL-24 Tg mice further confirmed that IL-24 is a classic cytokine like IL-20 and IL-22. Although it is possible that IL-24 may induce growth arrest or apoptosis for certain types of cells in vitro (21,22), the postnatal lethality and psoriatic skin phenotype as a result of hyperplasia in the epidermis observed for IL-24 Tg mice raise potential serious safety issues for using IL-24 (also known as MDA-7 before it was shown as a cytokine) as an anticancer agent in gene therapy (1,23).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 13, another cytokine involved in B lymphocytes activation, impedes leukemic cells apoptosis induced by interleukin 2 in vitro (Chaouchi et al, 1996). Interleukin 24 triggers apoptosis in CLL cells recruited to the cell cycle, by the inactivation of STAT3 kinase thus stabilizing expression of p53 (Sainz-Perez et al, 2008).…”
Section: Influence Of Chemokines On the Survival Of Cll Cellsmentioning
confidence: 99%